(untitled) (Asian Journal of Social Science Studies, 2019)
Semiotics is an indispensable theory of decoding images in modern times. In this paper, I will focus on three important scholars in the semiotics study area who are Saussure, Peirce and Barthes, their theories are extremely important and useful for helping us analyse advertisements. In this case, I use their theories to analyse two luxury perfume advertisements which is Dior J’adore and Burberry London, and can understand the meanings and structures of the advertisements by the theory of semiotics. These semiotic theories explain symbols in print advertisements of these luxury brands from the perspective of Semiotic, to explore the reasons of success of print advertisements of luxury brands and connotation meanings behind extension meanings from these image symbols. It is necessary to master some features of symbols well during advertisements design, sophisticated symbol design during advertisements design can improve texture and level of advertisements as well as spread messages accurately, achieving the unity of beauty and practicality.